The Confucian ethic and the spirit of East Asian police: a comparative study in the ideology of democratic policing - Martin, Jeffrey T. (Crime, law and social change, 2014)
This paper is an empirical study in comparative police ideology. It describes cultural qualities that distinguish Taiwan’s idea of democratic policing from comparable ideas in other places. I examine the historical process by which Taiwan’s police came to be organized around the population registry (the hukou). This process has institutionalized a Confucian understanding of civic virtue as an organizing principle in Taiwanese policing. Based on these historical and cultural observations, I formulate an ideal typical model of Taiwanese "policing through virtue" that can be compared to other stereotypical national policing styles such as Britain’s "policing by consent," America’s discretionary policing, and France’s formalist emphasis on division of power and rule of law.